Detection of cerebral embolic signals in patients with systemic lupus erythematosus. Issue 6 (24th February 2006) - Dahl, A; Omdal, R; Waterloo, K; Joakimsen, O; Jacobsen, E A; Koldingsnes, W; Mellgren, S I
Abstract : Background: Involvement of the CNS in systemic lupus erythematosus (SLE) is caused by several pathogenic mechanisms including cerebral embolism. Aim: To measure the frequency of microembolic signals (MES) by using transcranial Doppler (TCD) ultrasound and to assess their association with cerebral infarction, neuropsychological dysfunction, and biochemical, sonographic and clinical variables in an unselected group of patients with SLE. Methods: A 1-h TCD recording from the middle cerebral artery was carried out in 55 patients with SLE having a mean age of 46 (SD 13) years. MRI of the brain, carotid artery ultrasonography with intima–media thickness and atherosclerotic plaque assessments were carried out in addition to a broad biochemical and clinical assessment. All patients underwent a neuropsychological assessment. Results: Of the 55 patients, MES were detected in 5 (9%) and cerebral infarcts were found in 9 (18%). A significant association was found between MES and cerebral infarcts and considerably more neuropsychological deficits were found in MES-positive patients compared with the negative group. MES were not associated with other clinical, sonographic and biochemical factors believed to be associated with cerebral embolism. Conclusions: Cerebral embolism may be one of the important mechanisms responsible for the high prevalence of cerebrovascular events and the neuropsychological deficits observed in patients with SLE. Although the number of MES-positive patients was small, the lack of a significant association between MES and other known risk factors for MES suggests a complex pathogenesis for the embolisation in these patients.